2008
DOI: 10.1016/j.cub.2007.12.050
|View full text |Cite
|
Sign up to set email alerts
|

STIM1 Is a MT-Plus-End-Tracking Protein Involved in Remodeling of the ER

Abstract: Stromal interaction molecule 1 (STIM1) is a transmembrane protein that is essential for store-operated Ca(2+) entry, a process of extracellular Ca(2+) influx in response to the depletion of Ca(2+) stores in the endoplasmic reticulum (ER) (reviewed in [1-4]). STIM1 localizes predominantly to the ER; upon Ca(2+) release from the ER, STIM1 translocates to the ER-plasma membrane junctions and activates Ca(2+) channels (reviewed in [1-4]). Here, we show that STIM1 directly binds to the microtubule-plus-end-tracking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
424
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(448 citation statements)
references
References 17 publications
20
424
0
1
Order By: Relevance
“…STIM1 comet-like structures are seen as ER tubules extend with the growing microtubules, but STIM1 comet movements cease after store depletion-induced clustering, indicating that the association with microtubules may be a distinct function from CRAC channel activation (Baba et al, 2006;Grigoriev et al, 2008). In HEK293 cells, microtubule depolymerizaton did decrease CRAC current, but it had little effect on store induced STIM1 clustering (Smyth et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…STIM1 comet-like structures are seen as ER tubules extend with the growing microtubules, but STIM1 comet movements cease after store depletion-induced clustering, indicating that the association with microtubules may be a distinct function from CRAC channel activation (Baba et al, 2006;Grigoriev et al, 2008). In HEK293 cells, microtubule depolymerizaton did decrease CRAC current, but it had little effect on store induced STIM1 clustering (Smyth et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…STIM1 colocalizes with tubulin and plays a role in attaching ER membranes to the growing ends of microtubules (Baba et al, 2006;Smyth et al, 2007;Grigoriev et al, 2008), so we reasoned that microtubules might play a role in cap formation. In cells treated with colchicine to disrupt microtubules, STIM1 localized to blebs that protruded from the top of the cell instead of forming a normal cap (Supplemental Figure S4, A and B).…”
Section: An Intact Cytoskeleton Is Required For Normal Cap Formationmentioning
confidence: 99%
“…The mechanism and proteins involved in regulating ER movement during mitosis are not well understood; however, it was recently shown that phosphorylation of STIM1 is required to prevent the ER membrane from associating with the mitotic spindle (Smyth et al 2012). STIM1 is an integral membrane protein that binds to EB1, a microtubule (MT) plus tip binding protein, that will be further discussed in a subsequent section (Grigoriev et al 2008). During mitosis, STIM1 is phosphorylated, resulting in dissociation from EB1.…”
Section: Er During Mitosismentioning
confidence: 99%
“…TAC movements depend on tethering between the ER protein, STIM1, and an MT plus end-binding protein, EB1 (Fig. 3B, top panel) (Grigoriev et al 2008). The ER sliding mechanism accounts for the majority of ER dynamics in the cell and occurs through a machinery involving kinesin-1 and dynein MT motors that pull ER tubules along the sides of established MTs (Wozniak et al 2009).…”
Section: Er Dynamics and Assemblymentioning
confidence: 99%
“…When growing microtubules cross the ER, the microtubule tip-binding protein EB1 binds to STIM1 and pulls out a new ER tubule through a "tip attachment complex" mechanism (Grigoriev et al 2008;Honnappa et al 2009). Although this interaction is weakened by store depletion and does not appear necessary for puncta formation (Grigoriev et al 2008), one could imagine that STIM1-laden ER tubules are propelled in this way toward the cell periphery by microtubules, and when they encounter local sites of elevated IP 3 , local ER depletion releases the tubule near the PM with STIM1 primed to interact with the PM and establish or stabilize a junction. Interestingly, in two EM studies, store depletion caused the number of ER-PM junctions to increase, and overexpression of STIM1 further amplified this effect Orci et al 2009).…”
Section: Accumulation Of Stim At Er-pm Junctionsmentioning
confidence: 99%